Thermodynamic study of high thermal stability Carbon Dots. Issue 1 (1st January 2022) - Rimal, Vishal; Srivastava, P.K.
Abstract: Carbon Dots (CDs) in the recent years have been found to exhibit exceptional thermal stability. The superior nature CDs demonstrate in their physical, chemical, optical and conductive properties together with their low cytotoxicity make them a true contender to conventional inorganic counterparts. In this study the traditional thermodynamic properties that support the high thermal stability of CDs have been investigated. The thermal stability of CDs has been found to have a superior relationship with numerous parameters thereby paving a strong evidence for further research and advancement in the field. This result will further help in the development of organic nanoparticles which can be employed in environments where high-temperature resistance is a crucial requirement.